2016
DOI: 10.1007/jhep07(2016)152
|View full text |Cite
|
Sign up to set email alerts
|

The gauge-Higgs legacy of the LHC Run I

Abstract: The effective Lagrangian expansion provides a framework to study effects of new physics at the electroweak scale. To make full use of LHC data in constraining higher-dimensional operators we need to include both the Higgs and the electroweak gauge sector in our study. We first present an analysis of the relevant di-boson production LHC results to update constraints on triple gauge boson couplings. Our bounds are several times stronger than those obtained from LEP data. Next, we show how in combination with Hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
176
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(185 citation statements)
references
References 84 publications
4
176
0
Order By: Relevance
“…The c g , c t and c b parameters are chosen in the ballpark suggested by the studies of refs. [83][84][85], while still keeping the inclusive cross section within about 20% of its SM value, Indeed, many combinations of c g , c t and c b can be found which mildly affect the total cross section, while significantly changing the shape of the spectrum.…”
Section: Jhep03(2017)115mentioning
confidence: 98%
See 1 more Smart Citation
“…The c g , c t and c b parameters are chosen in the ballpark suggested by the studies of refs. [83][84][85], while still keeping the inclusive cross section within about 20% of its SM value, Indeed, many combinations of c g , c t and c b can be found which mildly affect the total cross section, while significantly changing the shape of the spectrum.…”
Section: Jhep03(2017)115mentioning
confidence: 98%
“…Many groups translated the data already collected by the LHC as well as earlier experiments into bounds on the Wilson coefficients of dimension-six SMEFT operators (see e.g., refs. [80][81][82][83][84][85]). …”
Section: Jhep03(2017)115mentioning
confidence: 99%
“…They are presently known to agree with the SM within a few per cent (For a combined analysis of LEP and Run I LHC data, see e.g. [14]), which translates into stringent limits on the dimension-6 operators.…”
Section: Preliminary Technicalitiesmentioning
confidence: 99%
“…For instance in the recent theoretical analysis of (Butter et al, 2016) it was concluded that diboson measurements at the LHC set better bounds on operators that contribute to aTGCs than LEP. The analysis of (Butter et al, 2016) is not incorrect. The LHC can indeed measure VBF and diboson production at high p T enormously better than LEP.…”
Section: Eft Interpretation Of Sm Measurementsmentioning
confidence: 99%
“…In (Butter et al, 2016) a fit was performed demonstrating the increased sensitivity that the LHC had from Run I compared to LEP, an example being shown in Figure 4. However, this increased sensitivity as described in (Butter et al, 2016) comes from the high p T regions available at the LHC.…”
Section: Eft Interpretation Of Sm Measurementsmentioning
confidence: 99%